Diesel Engine Performance Enhancement Using Thermal Insulation - P. Vijaya Rao, R. Subash, K. Sreenivasa Reddy, K. Ravi Kumar (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Energy conservation and emissions have become of increasing concern over the past few decades. Asautomobiles are one of the major sources of energy consumption and urban emissions, engineersconcerned are under significant pressure